POLA KOMUNIKASI LINTAS BUDAYA SANTRI DI PONDOK PESANTREN DARUL QUR’AN KECAMATAN PERCUT SEI TUAN KABUPATEN DELISERDANG - Ilham Sani; M. Joharis; Muhammad Zul Akbar Syah; Wahyudi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe and understand the pattern of cross-cultural communication of Santri at Darul Qur'an Islamic Boarding School and the obstacles experienced by Santri in communicating cross-culturally with other Santri. This research is a descriptive study using a qualitative approach in order to obtain broader and more in-depth information about the matters being discussed in this research. Techniques used in data collection include field observations, interviews and documentation. The data analysis techniques used in this study are data analysis techniques from Miles and Huberman, namely: data reduction, data presentation and verification or conclusions. The results of this study indicate that cross-cultural communication is a process of exchanging thoughts and meanings between people of different cultures. When this communication occurs between people of different origins, between ethnic groups (interethnical), racial groups (interracial) or language communication (intercommunal) it is called cross-cultural communication. Cross-cultural communication from members of different cultures plays a role in human behavior, for example, the behavior of students from outside the region conforms to the local culture, so that students from outside the region behave according to the local culture. Keywords: Communication, Cross Culture, Students, Islamic boarding school